2011
DOI: 10.1128/mcb.05103-11
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane Protein 198 Promotes LRP6 Phosphorylation and Wnt Signaling Activation

Abstract: Wnt/␤-catenin signaling is fundamental in embryogenesis and tissue homeostasis in metazoans. Upon Wnt stimulation, cognate coreceptors LRP5 and LRP6 ([LRP5/6] low-density lipoprotein receptor-related proteins 5 and 6) are activated via phosphorylation at key residues. Although several kinases have been implicated, the LRP5/6 activation mechanism remains unclear. Here, we report that transmembrane protein 198 (TMEM198), a previously uncharacterized seven-transmembrane protein, is able to specifically activate L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 58 publications
1
30
0
Order By: Relevance
“…Several protein kinases, including glycogen synthase kinase-3 and casein kinase-1γ, have been shown to phosphorylate this Wnt coreceptor (27). A recent study showed that transmembrane protein 198 can promote LRP6 phosphorylation and Wnt signaling activation by recruitment of casein kinase family proteins (28). Another report showed that salinomycin is able to overcome multidrug resistance mediated by the ATPbinding cassette transporter p-glycoprotein 170 (29).…”
Section: Discussionmentioning
confidence: 99%
“…Several protein kinases, including glycogen synthase kinase-3 and casein kinase-1γ, have been shown to phosphorylate this Wnt coreceptor (27). A recent study showed that transmembrane protein 198 can promote LRP6 phosphorylation and Wnt signaling activation by recruitment of casein kinase family proteins (28). Another report showed that salinomycin is able to overcome multidrug resistance mediated by the ATPbinding cassette transporter p-glycoprotein 170 (29).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this notion, slc35c1 OE are more sensitive to elevated Lrp6 than wild-type embryos. Previous studies of Lrp6 mediated regulation of Wnt signaling indicate that the presence of Lrp6 does not necessarily result in Wnt activation because Lrp6 must be phosphorylated and internalized to activate Wnt signaling (Liang et al, 2011) and reviewed in (Cruciat & Niehrs, 2013). In addition, Lrp6 is known to form higher order complexes with multiple factors that can influence the composition of the higher order complexes as well as whether or not the Wnt signal is transduced.…”
Section: Discussionmentioning
confidence: 99%
“…Tiam1-C1199 was subcloned into the pEGFP-N1 vector to obtain Tiam1-C1199-GFP. CK1 constructs have been described previously (34). Five fragments of Tiam, 1named Tiam1-A (aa 1-392), Tiam1-B (aa 393-750), Tiam1-C (aa 751-1000), Tiam1-D (aa 1001-1250), and Tiam1-E (aa 1251-1591) were subcloned into the pcDNA 3.1 vector fused with an N-terminal Myc tag.…”
Section: Methodsmentioning
confidence: 99%